Collaborative Writing Technique (CWT): Elevators Students’ Writing Performance - Nurjanah, Siti; Firdaus, Masagus; Mulyadi, Mulyadi (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
This study aimed to improve the students’ writing skill and their activeness through collaborative writing technique (CWT). The subject were 25 students of phase E at SMA Insan Cendikia Sriwijaya Palembang in academic year 2023/2024. Data collection technique used writing test and observation. This study is classroom action research (CAR) which was conducted into three cycles. Each cycle consisted of four stages; planning, action, observation and reflection. The result in Cycle I, the average score is 68.08 with the classical achievement 52%. In Cycle II, the average score is 79.44 with the classical achievement 76%. The last, Cycle III has 87.24 average score with 92% as the classical achievement. Those increasement obtained the success criteria of this study. In conclusion, the implementation of CWT could improve the phase E students’ writing skill at SMA Insan Cendikia Sriwijaya Palembang.